PENGARUH EKSTRAK SELEDRI (Apium graveolens) TERHADAP KADAR TRIGLISERIDA Penelitian Eksperimental pada Tikus Putih Kondisi Hiperlipidemia - Siti Nur Cholishoh; Masyhudi (PT. Hasba Edukasi Mandiri, 2026)
Hyperlipidemia is a disorder of lipid metabolism characterized by increased total cholesterol, low-density lipoprotein (LDL), and triglyceride levels, as well as decreased high-density lipoprotein (HDL), largely associated with oxidative stress. Although the use of synthetic drugs such as simvastatin is effective in reducing lipid levels, these drugs may cause adverse side effects. Therefore, safer natural alternatives are needed, including celery (Apium graveolens), which contains flavonoids and antioxidants that have the potential to reduce blood triglyceride levels. This study aimed to determine the effect of celery (Apium graveolens) extract on triglyceride levels in hyperlipidemic white rats. This experimental study employed a pre-test and post-test control group design involving 32 male white rats divided into four groups: normal control, positive control, treatment group 1 (celery extract 10 mg/200 g body weight), and treatment group 2 (celery extract 500 mg/200 g body weight). Triglyceride levels were measured before and after treatment using a spectrophotometer. The mean triglyceride levels were 76.12 mg/dL in group K1, 98.01 mg/dL in group K2, 115.77 mg/dL in group K3, and 90.86 mg/dL in group K4. Normality testing showed that all groups had normal data distribution (p>0.05), and homogeneity testing indicated homogeneous variances (p=0.615). One-way ANOVA revealed a statistically significant difference among groups (p<0.001). Post Hoc LSD analysis demonstrated significant differences between all groups (p<0.05). In addition, the Paired t-test showed a significant difference between pre- and post-treatment triglyceride levels in all groups (p<0.01). The data analysis indicates that celery extract significantly reduces triglyceride levels in hyperlipidemic white rats.